Application of Sociodrama Techniques in Group Guidance to Improve Students' Ability to Manage Conflict in Junior High Schools - Muhammad Zuhri Abu Nawas (Jurnal Konsepsi, 2021)
This study focuses on the ability to manage conflict between students before and after being given sociodrama treatment in the experimental group, the level of conflict management ability between students in the control group based on the results of the pretest and post-test, differences in the ability to manage conflict between the groups that were treated with sociodrama (experimental) and control group (which was not treated). This research is quantitative research with Nonrandomized Control Group Pretest-Postest Design. The population data obtained is 1024 starting from class VII to class IX at SMP Negeri 2 Bulukumba using a sample of 42 students. Those who act as independent variables are teachers (X), while those who act as dependent variables are students (Y). The results showed that the description of students' ability to manage conflict had increased after being treated in the form of sociodrama, hypothesis testing showed a significant difference in the ability of students to manage conflict between before and after being given treatment in the form of sociodrama. Students' ability to manage conflict is higher than before being given sociodrama treatment.